Efeitos da combinação entre estrutura de prática e frequência de conhecimento de resultados na aquisição de habilidades motoras - Maicon Rodrigues Albuquerque (2010)
The purpose of this study was to investigate the effects of combination of practice schedule and relative frequency of knowledge of results. One hundred and twenty volunteers were randomly assigned in 12 groups: 1) constant - 100% KR in parameter and GMP (C100-100), 2) onstant-100% KR in parameter and 50% KR in GMP (C100-50), 3) constant-50% KR in parameter and 100% KR in GMP (C50-100), 4) constant-50% KR in parameter and 50% KR in GMP (C50-50), 5) Parameter - 100% KR in parameter and GMP (PAR100-100), 6) Parameter - 100% KR in parameter and 50% KR in GMP (PAR100-50), 7) Parameter - 50% KR in parameter and 100% KR in GMP (PAR50-100), 8) Parameter -50% KR in parameter and 50% KR in GMP (PAR50-50), 9) GMP - 100% KR in parameter and GMP (GMP100-100), 10) GMP - 100% KR in parameter and 50% KR in GMP (GMP100-50), 11) GMP - 50% KR in parameter and 100% KR in GMP (GMP50-100), 12) GMP - 50% KR in parameter and 50% KR in GMP (GMP50-50). The task consisted of press a specific sequence from the keypad was conducted in two phases. In the acquisition phase, the constant groups practiced the task with the 1400ms total time and the relative time of 22.2% -44.4% -33.3%, while random groups practice (parameter) performed the task with total times of 1200, 1400 and 1600ms and the relative time of 22.2% -44.4% -33.3%. The groups of random practice (GMP) practiced the task with the total time 1400ms and times for 22.2% -44.4% -33.3%, 44.4% -33.3% -22.2% and 33.3% -22.2% -44.4%. In the test phase, all groups practiced with total time of 1400ms and the relative time of 22.2% -44.4% -33.3%, in retention test, while in transfer test all groups practiced in the total time of 1800ms and relative time of 22.2% -55.5% -22.2%. The results demonstrated, in a general way, maintenance of acquisition phase performance only in retention test, what suggested learning occurrence. However, it was not verified significant differences among groups in retention and transfer tests. It was conclude that there was not effect of the combination between practice schedule and relative frequency of knowledge of results.